Dinoflagellaten-Zysten im Spätquartär des europäischen Nordmeeres: Palökologie und Paläo-Ozeanographie - Matthiessen, Jens (GEOMAR Forschungszentrum für marine Geowissenschaften, 1991)
Dinoflagellate cysts have been investigated in surface from the Norwegian-Greenland Sea and short sediment cores Norwegian Sea spanning the last 15,000 years. sediments from the The distribution of single species and assemblages is related to the bathymetry and oceanography of the Norwegian-Greenland Sea. Oceanographic fronts can be recognized in the distribution of species and assemblages. Round protoperidinoid cysts, MuZtispinuZa minuta s.l. and HaZodinium spp., characterize the assemblages from the East Greenland Shelf. Nematosphaeropsis Zabyrinthus and ?Impagidinium paZZidum dominate the assemblages in the central leeland and Greenland Seas. Operculodinium centrocarpum is important in the marginal area of the Arctic domain and dominates clearly the assemblages from the Norwegian Sea. Assernblages from the shelf of north leeland are marked by cysts of Peridinium faeroense. The distribution pattern of single species and assemblages reveals that relatively warm north Atlantic waters only pass through the Faeroe Shetland Canal into the Norwegian-Greenland Sea and further · up into the eastern Arctic Ocean and the Barents Sea. In the southern Norwegian Sea the Atlantic water masses are already modified by advection of surface waters from the North Sea. The development of the Norwegian current has been reconstructed by means of dinoflagellate cysts since termination r •. North Atlantic water masses have almost always influenced the surface water masses in the last 15,000 years. Since ca. 12,000 to 13,000 BP, the influence of warmer North Atlantic waters increased significantly in the NorwegianGreenland Sea. The modern circulation system was established around 10,000 BP. First, the Norwegian current was cooler and less saline, and then obtained its modern hydrographic properties around 6,000 to 7,000 BP. A slight change towards cooler conditions is documented in the western marginal areas in the last 2,000 to 3,000 years. Changes in the oceanography of the Norwegian-Greenland Sea must be related to modifications in ...